2021
DOI: 10.2147/ndt.s297975
|View full text |Cite
|
Sign up to set email alerts
|

MiR-195-5p Ameliorates Cerebral Ischemia-Reperfusion Injury by Regulating the PTEN-AKT Signaling Pathway

Abstract: Background MiR-195-5p has been shown to play crucial roles in tumor inhibition, but its biological functions in cerebral ischemia-reperfusion (I/R) injury are unclear. Methods To mimic cerebral I/R injury, mice were induced by transient middle cerebral artery occlusion (MCAO). Human brain microvascular endothelial cells (HBMVECs) were treated with oxygen-glucose deprivation (OGD) to mimic I/R injury in vitro. The expression of miR-195-5p and PTEN was detected by qRT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Moreover, p-CREB is involved in neuronal apoptosis processes, which is mediated partially by BDNF. p-CREB overexpression inhibited neuronal apoptosis, whereas the inhibition of CREB activity accelerated neuronal apoptosis (Ren et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, p-CREB is involved in neuronal apoptosis processes, which is mediated partially by BDNF. p-CREB overexpression inhibited neuronal apoptosis, whereas the inhibition of CREB activity accelerated neuronal apoptosis (Ren et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…According to another study, mTOR signal pathway achieved a vital function for protection against ischemic stroke (Li et al, 2021b). Moreover, Ren et al, confirmed that PI3K/Akt/mTOR signaling pathway could protect nerve energy cells by participating in oxidative stress and negatively regulating apoptosis (Ren et al, 2021). Consistent results were achieved here, which demonstrated that daidzein significantly up-regulated the expression levels of p-PI3K, p-Akt and p-mTOR, while LY294002, a specific inhibitor of PI3K, noticeably reversed the aforementioned effects of daidzein.…”
Section: Discussionmentioning
confidence: 97%
“…HIE can lead to neurodevelopmental and cognitive impairment in survivors, with or without motor impairment [ 5 ] and is considered to be the main cause of neonatal death [ 24 , 25 ]. SF pre-treatment and post-treatment can protect the brain [ 9 ], but the neuroprotective effect of SF pretreatment on HIE is limited [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the sections were dehydrated with ethanol gradient, cleared with xylene, and sealed with sealing resin (YT2494, YITA Biotechnology Co., Ltd, Beijing, China). Morphological image analysis system JD801 (JD801, Jeda Technology Co. Ltd., Nanjing, China) was used to observe the morphological changes of neurons after HE staining in cerebral cortex of different groups of rats, and the images were randomly collected [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Wang et al ( 12 ) elucidated that miR-186-5p was upregulated and induced apoptosis in an oxygen and glucose deprivation/reperfusion (OGD/R) model by targeting insulin-like growth factor (IGF)-1. Conversely, Ren et al ( 13 ) reported that overexpression of miR-195-5p efficiently enhanced cell viability, while it reduced lactate dehydrogenase (LDH) release and the apoptotic rate in OGD-treated endothelial cells by targeting PTEN. In addition, miR-124-5p could reduce ROS production and improve the inflammatory microenvironment to attenuate cerebral I/R injury by targeting NOX2 ( 14 ).…”
Section: Introductionmentioning
confidence: 99%